Active proteases in nephrotic plasma lead to a podocin‐dependent phosphorylation of VASP in podocytes via protease activated receptor‐1. Issue 5 (22nd February 2013) - Harris, Jessica J; McCarthy, Hugh J; Ni, Lan; Wherlock, Matthew; Kang, HeeGyung; Wetzels, Jack F; Welsh, Gavin I; Saleem, Moin A
Abstract Focal segmental glomerulosclerosis (FSGS) is associated with glomerular podocyte injury. Podocytes undergo dramatic changes in their actin structure, with little mechanistic insight to date into the human disease. Post‐transplantation recurrence of FSGS is the archetypal form of the disease caused by unknown circulating plasma 'factors'. There is increasing indication that plasma protease activity could be central to this disease. Using clinical plasma exchange material, collected from patients in relapse and remission stages of disease, the effects of FSGS plasma on human conditionally immortalized podocytes (ciPods) were studied. We show that vasodilator stimulated phosphoprotein (VASP) is phosphorylated in response to relapse plasma from ten consecutively tested patients, and not in response to paired remission plasma or non‐FSGS controls. The phosphorylation signal is absent in human podocytes carrying a pathological podocin mutation. To test for a plasma ligand, inhibition of proteases in relapse plasma leads to the loss of VASP phosphorylation. By the use of siRNA technology, we show that proteases in the plasma signal predominantly via protease activated receptor‐1 (PAR1) to VASP. Mechanistically, FSGS plasma increases podocyte motility, which is dependent on VASP phosphorylation. These data suggest a specific biomarker for disease activity, as well as revealing a novel and highly specific receptor‐mediated signalling pathway to the actin cytoskeleton. Copyright © 2012 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.